Editorial: The Acoustic Characteristics of Religious Buildings - El-Basheer , Tarek M. (International Journal of Architectural Engineering Technology, 2022)
The acoustical experience of people in places of worship is not accurately captured by physical measures of building acoustics. While many studies concentrate on the acoustics of buildings, aural architecture analysis which provides a more thorough knowledge of the aural experience by considering perceptual and cultural factors in addition to physical ones receives less attention. Worship areas need intricate acoustical settings that enable both clear sound perception and the enjoyment of aesthetic sound. There is a need for more research on the relationship between the qualitative and quantitative acoustical features of religious buildings since this experience can have emotional consequences through the sense of sound.